Village Fund Allocation Practice: The Investigation of Accountability and Transparency - Putu Prema Sulistyaning Putri; Rhosalina Damayanti; Aprina Nugrahesthy Sulistya Hapsari (Universitas Pendidikan Ganesha, 2021)
This research aims to describe the practice of accountability and transparency in the management of village funds in Gedangan Village, Semarang Regency. This research used qualitative descriptive method through in-depth interviews with the research stages in the form of data reduction, data presentation, and drawing conclusions. The results indicate that the management of village funds in Gedangan Village has been implemented in accordance with the principles of accountability and transparency. However, there are still some obstacles such as changes to government regulations requiring adjustments to village fund management, the lack of effectiveness of the official village website as a means of distributing information, and a lack of public awareness to read information about the village funds. The implication of this research is as an evaluation of the government of Gedangan Village in improving the means of village information disclosure and to encourage community participation in the management of village funds.